ZIRCONS FROM ROCKS OF THE MURZINKA-ADUI METAMORPHIC COMPLEX: GEOCHEMISTRY, THERMOMETRY, POLYCHRONISM, AND GENETIC CONSEQUENCES - G. Yu. Shardakova; S. V. Pribavkin; A. A. Krasnobaev; N. S. Borodina; M. V. Chervyakovskaya (Геодинамика и тектонофизика, 2021)
Transformation of the oceanic crust into the continental one in orogenic belts is an important problem in petrological studies. In the paleocontinental sector of the Urals, a key object for tracing the stages of metamorphism and investigating the origin of anatectic granites is the Murzinka-Adui metamorphic complex. We have analyzed trace elements in zircons and established their genesis, sources, crystallization conditions, and stages of metamorphic events and granite generation in this complex. Zircons compositions were determined by the LA-ICP-MS method. Temperatures were calculated from Ti contents in the zircons. We distinguish three geochemical types of zircons, which differ in the ratios of light and heavy REE, U, Th, Ti, Y and show different values of Ce- and Eu-anomalies and Zr/Hf ratios, which are indicative of different crystallization conditions, as follows. Type I: minimal total LREE content; clear negative Eu- and Ce- anomalies; features of magmatic genesis; crystallization temperatures from 629 to 782 °C. Type II: higher contents of Ti, La, and LREE; low Ce-anomaly; assumed crystallization from highly fluidized melts or solutions. Type III: low positive Eu-anomaly; high REE content; low Th/U-ratio; zircons are assumed to originate from a specific fluidized melt with a high Eu-concentration. Ancient relict zircons (2300–330 Ma) in gneisses and granites show features of magma genesis and belong to types I and II. Such grains were possibly inherited from granitoid sources with different SiO2 contents and different degrees of metamorphism. Based on the geological and petrogeochemical features and zircon geochemistry of the Murzinka-Adui complex, there are grounds to conclude that the material composing this complex was generated from the sialic crust. The main stages of metamorphism and/or granite generation, which are traceable from the changes in types and compositions of the zircons, are dated at 1639, 380–370, 330, and 276–246 Ma. Thus, transformation of the oceanic crust into the continental one was a long-term and complicated process, and, as a result, the thickness of the sialic crust is increased in the study area.